Epidemiological characterization of the main health indicators of COVID-19 in Teresina-PI, Brazil: a brief analysis (Research, Society and Development, 2020)
This study aimed to analyze the epidemiological profile of the main health indicators of COVID-19 in Teresina-PI. This is an epidemiological, descriptive and quantitative resurvey of cases reported by COVID-19 in the city of Teresina-PI, from March 13 to July 12, 2020. The data were analyzed from there ports of the epidemiological bulletin of health in the city provided by the Municipal Health Foundation (FMS). The variables evaluated were age group, gender, lethality rate, comorbidities, deaths, confirmed cases, to ten largest neighbor hoods with confirmed cases, mean, median, standard deviation, variance and analysis of the evolution in the number of infections and deaths by COVID- 19. Data were tabulate dusing the TABNET and Microsoft Office Excel 2019 programs 10,914 cases of COVID-19 were confirmed in the city of Teresina-PI and there was an increasing trend in the frequency of notification. There was a predominance of confirmed cases in females (n = 6058; 55.51%), aged between 30 and 39 years (n = 2,799; 25.6%) and 40 to 49 years (n = 2,012; 18,5%). While, in relation to those who died, it was in the male gender (n = 303; 55.9%), with a lethality of 6.23%, and in the age group of 70 years to 79 (n = 134; 25.0 %) and 80 to 89 (n = 126; 23.2%), with a lethality of 45.3% and 62% respectively. And 82% of patients had comorbidities. There was also a higher incidence of deaths in the neighborhoods of Itararé, 27.50%, followed by Promorar with 15.50%. However, case confirmations 20% Itararé and 14% Mocambinho. The behavior of the pandemic is rising in the city of Teresina-PI, which highlights the need for more containment measures.